After We Collided - Book 2 - Todd, Anna (New York : Gallery Books, 2014)
"Book two of the After series--the Internet sensation with millions of readers. Tessa didn't plan on meeting H. during her freshman year of college. But now that she has, her life will never be the same same"--
Keywords: College students -- Fiction; Man-woman relationships -- Fiction; Universities and colleges -- Fiction; FICTION / Romance / Contemporary; FICTION / Contemporary Women; Romance fiction; Campus fiction